Meningkatkan Kesadaran Tanggung Jawab Siswa SMP Melalui Penggunaan Teknik Klarifikasi Nilai - Romia Hari Susanti (JKI (Jurnal Konseling Indonesia), 2015)
One important character values instilled in students is the awareness responsibility. Values clarification can increase the insight of diversity values awareness responsibility, because for its implementation has several stages include selecting, respect, action, and self reflection. This study aims to examine the increased junior high school student’s awareness responsibility through values clarification technique using a quasi-experimental research design types one group pretest-posttest design. Subjects were grade ten junior high school students who have the awareness responsibility criteria is low. Based on the results value clarification effective to increase awareness responsibility junior high school students.